UPAYA GURU DALAM MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN METODE MINDMAPPING PADA MATA PELAJARAN IPA DI SDN DURI KEPA 03 - Melly Nurhayatun; Harlinda Syofyan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The research was conducted in class III B at SDN Duri Kepa 03 in the odd semester of the 2021/2022 academic year with 32 students. The stages of this research were carried out in two cycles: (1) the planning stage, (2) the action implementation stage, (3) the observation stage, and (4) the reflection stage. Data collection in the study included observation sheets of student learning activities, teacher observation sheets of activities when the mind mapping learning method was used, and test questions that measure student learning outcomes in terms of material changes in the shape of objects used. Data analysis techniques in this study used qualitative and quantitative analysis. The results of this study indicate that the use of the mind mapping learning method on changing the shape of objects can improve student learning outcomes at SDN Duri Kepa 03. These results can be seen from Cycle I, where the average class achievement was 72.81 at the completeness level of 20 students (62, 5%), while in Cycle II the class average was 72.81 at the completeness level of 28 students (87.5%). score increases. By using mind mapping techniques in this learning activity, you will find that learning outcomes and students' responsiveness to learning materials increase. Classroom learning encourages students to be more active and curious about what is being taught.